A facile green "wastes-treat-wastes" strategy: Electrogenerated chloramines for nanofiltration concentrate recirculation. (1st January 2023) - Du, Xing; Li, Ziyang; Peng, Zhitian; Zhang, Zhong; Xiao, Mengyao; Wang, Zhihong; Yang, Yang; Li, Xianhui
Abstract: Use of nanofiltration (NF) membrane to reuse the secondary wastewater suffers from severer biofouling and refractory concentrate. To realize sustainable NF membrane processes in water purification, the electro-oxidation (EO) process using boron-doped diamond (BDD) anodes was applied in current study to treat the NF concentrate for removal of organic contaminates and nutrients using simultaneously controllable in-situ generation of chloramines. The electrolytic effluent would be mixed with the raw secondary wastewater as the feed of subsequent NF process for conducting chloramination to mitigate membrane biofouling. It was found that under a constant current density of 30 mA/cm 2, the chloramine formed with the electrolysis while its concentration reached the maximum at 30 min of electrolysis when NH3 –N was 7 mg/L and Cl − concentration was below 500 mg/L. The complete elimination of antibiotics and bacteria can be attained in the hybrid NF-EO process thanks to the in-situ simultaneous generation of large amount of chloramine. In particular, the membrane biofouling was effectively alleviated to maintain a stable permeate flux during the 160-h period of sustainable operation. Our study provides a promising "wastes-treat-wastes" strategy for sustainable reuse of secondary wastewater. Graphical abstract: Image 1 Highlights: An electro-oxidation (EO) process was applied to recirculate NF concentrate. Chloramines were generated controllably using EO process. EO process was proven for efficient removal of NH3 –N and refractory organics. The membrane biofouling was alleviated with electrogenerated chloramines. NF-EO process functions as a "wastes-treat-wastes" strategy for wastewater reuse.